2002
DOI: 10.1002/jmv.10208
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C virus particles of different density in the blood of chronically infected immunocompetent and immunodeficient patients: Implications for virus clearance by antibody

Abstract: The purpose of this study was to analyse the influence of the humoral immune response on the generation and clearance of hepatitis C virus (HCV) RNA containing particles in the blood of chronically infected patients. Blood samples were fractionated by sequential flotation ultracentrifugation and HCV RNA was recovered in three fractions: low density of < 1.063 g/ml, intermediate density of 1.063-1.21 g/ml, and high density of > 1.21 g/ml. Serum low-density lipoproteins co-fractionated with the low-density parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
50
0
3

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(55 citation statements)
references
References 23 publications
2
50
0
3
Order By: Relevance
“…Our immunoprecipitation analysis showed that the LVPs contain both ApoB and ApoE. ApoB is found on all low-density lipoproteins, but the presence of ApoE is characteristic of VLDL We have found that HCV core, as well as glycoproteins E1 and E2, is present in fractions with densities below 1.08 g/ml from liver S6b (42) (Fig. 6), and this has allowed us to seek antibodies capable of immunoprecipitating these viral proteins.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…Our immunoprecipitation analysis showed that the LVPs contain both ApoB and ApoE. ApoB is found on all low-density lipoproteins, but the presence of ApoE is characteristic of VLDL We have found that HCV core, as well as glycoproteins E1 and E2, is present in fractions with densities below 1.08 g/ml from liver S6b (42) (Fig. 6), and this has allowed us to seek antibodies capable of immunoprecipitating these viral proteins.…”
Section: Discussionmentioning
confidence: 85%
“…A sample of 100 l from patient S6 or 1 ml from patients S7 to S9 was mixed with NaBr solution with a density of 1.063 g/ml and centrifuged at 146,000 ϫ g av (g av is the average centrifugal force) in a Beckman Type 50 Ti fixed-angle rotor (42). After sequential ultracentrifugation, three samples of 1 ml each were harvested from low-density ( Ͻ 1.063 g/ml), intermediate-density (1.063 g/ml Ͻ Ͻ 1.21 g/ml), and high-density ( Ͻ 1.21 g/ml) fractions.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been suggested that, in chronically infected patients, HCV circulates as low-density lipoprotein virus particles (1,40), with various density profiles depending on the stage of the infection at which the sample was obtained (9,43). The differences in density and infectivity have been attributed to the presence of host lipoproteins and antibodies bound to the circulating viral particles (22,43).…”
mentioning
confidence: 99%
“…10 The subjects' clinical presentation was compared to the differential HCV density fractions. Baseline and sequential liver function tests were performed and five out of six patients proceeded to liver biopsy for clinical purposes.…”
mentioning
confidence: 99%